Synthesis and Characterization of Diol, And Dicarboxylic acid from Oleic Acid (Latakia University Journal -Basic Sciences Series, 2020)
In this article, three diols were synthesized from oleic acid, which are  1,9- nonane diol, diester diol, and tetra ester diol. In addition to preparing dicarboxylic acids during the synthesis of previous diols, these diols are the most important monomers used in the synthesis of many biodegradable and thermoplastic polymers such as polyurethane, polyester, and polyamide ester, with wide medical and biological applications, given that they are linear structures and have hydroxyl functional groups at both ends of their linear chain. The structure of the resulting compounds was confirmed by using spectroscopic methods known as 1H-NMR and FT-IR spectroscopy. and we got these diols with a good yield, ranging between (72-90)%.